Analysis of STEM-Based Project-Based Learning Model on Physics Materials Referring to the Independent Curriculum - Syaifuddin Syaifuddin; Sarwi Sarwi; Hartono Hartono; Murbangun Nuswowati (International Conference on Science, Education, and Technology, 2022)
Abstrak. High school physics learning outcomes referring to the Regulation of the Minister of Education and Culture include aspect of understanding concept. The purpose of this study was to descriptively analyze the development and effectiveness of STEM-Project Based learning (STEM-PjBL) model in physics learning outcomes referring to the independent curriculum in Indonesia. This study used a descriptive qualitative research approach with data collection techniques through in-depth interviews, data observation, literature studies. The study was conducted in six Senior High Schools in Semarang from July 1st to August 31st, 2022. The data sources consisted of physics teachers, observation sheets and literature studies from published or perish (PoP). In the literature study, data collection was carried out based on the Scopus database with the keywords STEM Based Project based learning; Physics learning. The data analysis was carried out using Miles and Huberman (2014) model, which included the stages of data reduction, display, and verification. The results showed that most of the teachers who applied physics learning in the independent curriculum had not used the STEM-based PjBL learning model and still experienced many obstacles in developing learning scenarios, thus the outcomes of learning physics were still low. Supported by the results of literature study using PoP, it illustrates that the trend of physics publications from 2017-2022 is dominated by PjBL and STEM learning at the high school level. This study recommends that the availability of guides or manuals for implementing online and offline STEM-based PjBL learning model that can develop the aspects of scientific skills and product of the students learning is needed.